2017
DOI: 10.1016/j.jacc.2017.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Beta as a Target for Atherosclerosis Therapy

Abstract: Inflammatory pathways drive atherogenesis and link traditional risk factors to atherosclerosis and its complications. One inflammatory mediator has come to the fore as a therapeutic target in cardiovascular disease. The experimental and clinical evidence reviewed here support interleukin-1 beta (IL-1β) as both a local vascular and systemic contributor in this regard. Intrinsic vascular wall cells and lesional leukocytes alike can produce this cytokine. Local stimuli in the plaque favor the generation of active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
369
3
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 496 publications
(396 citation statements)
references
References 119 publications
(102 reference statements)
12
369
3
12
Order By: Relevance
“…GlycA is derived from glycosylation of five major acute phase inflammatory proteins and may be a more stable marker of systemic inflammation than some of the other traditional markers . Targeting inflammation has become increasingly recognized as an important CVD prevention strategy . Findings from the recent Canakinumab Anti‐inflammatory Thrombosis Outcome Study (CANTOS) further highlight that reductions in CVD, independent of lipids, can be made by targeting systemic inflammation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GlycA is derived from glycosylation of five major acute phase inflammatory proteins and may be a more stable marker of systemic inflammation than some of the other traditional markers . Targeting inflammation has become increasingly recognized as an important CVD prevention strategy . Findings from the recent Canakinumab Anti‐inflammatory Thrombosis Outcome Study (CANTOS) further highlight that reductions in CVD, independent of lipids, can be made by targeting systemic inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation plays a key role in the pathogenesis of cardiovascular disease (CVD), and recently inflammation has become a direct target of therapy for CVD prevention . High‐sensitivity C‐reactive protein (hsCRP), a marker of systemic inflammation, has been shown to be associated with incident CVD events .…”
Section: Introductionmentioning
confidence: 99%
“…New compounds that interfere with IL-1 and IL-6 signalling are under investigation 163,167 . The CANTOS trial 168 has revealed that anti-inflammatory therapy with canakinumab, a human monoclonal anti-IL-1β antibody, significantly reduced recurrent cardiovascular events in >10,000 stable patients who had residual inflammation after myocardial infarction, independent of lowered lipid levels 169 .…”
Section: Consequences Of Inflammageing For Cvdmentioning
confidence: 99%
“…The IL-1ra approach has had a modest benefit in overt inflammatory conditions such as rheumatoid arthritis (3) and a significant effect in anti-inflammatory conditions characterised by over activity of the inflammasome (4). The IL-1 pathway has considerable preclinical data to support its involvement in atherogenesis, the inflammatory response to fat feeding and the response to vessel wall response to injury (5)(6)(7). Whilst these studies, conducted as they were in laboratory animals have all been consistent with a hypothesis that IL-1 is atherogenic, human genetic studies…”
Section: S O C I a T E D M Y O C A R D I A L I N F A R C T I O N O Rmentioning
confidence: 89%